EVALUASI KEPATUHAN PENULISAN OBAT DALAM KARTU OBAT PENDERITA RAWAT INAP RUANG KUTILANG TERHADAP FORMULARIUM RUMAH SAKIT DI RSUP Dr. KARIADI SEMARANG PERIODE 2007 - sri susilowati; winarni winarni; saroja saroja (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2008)
ABSTRACTDrug formularium is a method used by hospital medical staff to evaluate and choose a drug for patient treatments from various available drug trade name preparations within hospital. Objective of this study was to evaluate prescription compliance on drug cards of Kutilang in-patients ward towards Dr Kariadi Hospital Formularium during 2007. Non experimental, retrospective and non analytical observational study design was done. Sample collected by a proportional stratified random sampling from Kutilang in-patient drug card during 2007. Data were compared to Dr Kariadi Hospital Formularium. When prescription of drugs trade name different with formularium but generic name available, it was considered as non-formularium A and non-formularium B if either trade name or generic name drugs were not present. The results showed there were 56.1% female patients and 43.9% male patient hospitalized in Kutilang ward during 2007, in which 30.4% was belong to Internal medicine patients. Total number of drugs used were 613 items consist of 46.8% generic drugs and 53.2% trade name (patent) drugs. Overall agreement of drug used to the formularium was 77.7%. The rank of drug prescription agreement were as follows, anesthesiologist and psychiatry both were 100% agree to formularium, cardiologist was 14.8% agree to non-formularium A and dermato-venerologist was 40.9% belong to non-formularium B. The higest rank of prescription based on treatment classes were immunosuppressant (92.9%) among formularium, anti diabetics (32.2%) among non-formularium A and ENT drugs (83.3%) among non-formularium B. Key words : formularium, compliance, in-patient, dr Kariadi Hospital